Remark on Random Attractors of Stochastic Non-Newtonian Fluid (Journal of Partial Differential Equations, 2018)
In this paper, we study the asymptotic behaviors of solution for stochastic non-Newtonian fluid with white noise in two-dimensional domain. In particular, we will prove the existence of random attractors in H.
Keywords: Random attractors; non-Newtonian fluid; stochastic equation; Ornstein-Uhlenbeck process